Languages of trauma : history, memory, and media - Leese, Peter; Köhne, Julia; Crouthamel, Jason (University of Toronto Press, 2021)
"This volume traces the distinct cultural languages in which individual and collective forms of trauma are expressed in diverse variations, including oral or written narratives, literature, comic strips, photography, theatre, and cinematic images. The central argument is that traumatic memories are frequently beyond the sphere of medical, legal, or state intervention. To address these different, often intertwined modes of language, the contributors provide a variety of disciplinary approaches to foster innovative debates and provoke new insights. Prevailing definitions of trauma can best be understood according to the cultural and historical conditions within which they exist. Languages of Trauma explores what this means in practice by scrutinizing varied historical moments from the First World War onwards and particular cultural contexts from across Europe, the United States, Asia, and Africa - striving to help decolonize the traditional Western-centred history of trauma, dissolving it into multifaceted transnational histories of trauma cultures."-- Provided by publisher.
Keywords: Psychic trauma in literature.; Psychic trauma in the theater.; Psychic trauma in motion pictures.; Psychic trauma in music.; Psychic trauma and mass media.; Memory in art.; Memory in literature.; Memory in motion pictures.; War films -- History and criticism.; War in literature.; Traumatisme psychique dans la littérature.; Traumatisme psychique au théâtre.; Traumatisme psychique au cinéma.; Traumatisme psychique dans la musique.; Traumatisme psychique et médias.; Mémoire dans la littérature.; Mémoire au cinéma.; Films de guerre -- Histoire et critique.; Guerre dans la littérature.; SOCIAL SCIENCE / Media Studies; Memory in art; Memory in literature; Memory in motion pictures; Psychic trauma and mass media; Psychic trauma in literature; Psychic trauma in motion pictures; Psychic trauma in music; Psychic trauma in the theater; War films; War in literature; World War I.; history.; media.; medical humanities.; memory.; post-traumatic stress disorder.; psychiatry.; psychology.; resilience.; shell shock.; trauma and medicine.; trauma in cinema.; trauma.; war and trauma.; Criticism, interpretation, etc.